Strenuous physical exercise and hematological indices of cardiovascular risk: the exception case of a 93-year-old man running a 100-km distance - Tarperi, Cantor; Salvagno, Gian Luca; Schena, Federico; Lippi, Giuseppe (Annals of Blood, 2017)
We describe here the variation of hematological and biochemical parameters in a 93-year-old man, who successfully completed a 100-km distance run. The athlete completed the trial at an average speed of 5.6 km/h. The red blood cell distribution width (RDW) increased immediately after crossing the finishing line and peaked 1 day afterward, displaying a 14% increase from baseline. The RDW then declined to a value still higher than the baseline after 1 week. The value of mean platelet volume (MPV) increased immediately after crossing the finishing line, decreased in the following 2 days and returned to baseline after 1 week. The serum concentration of cardiac troponin T (cTnT) peaked immediately at the end of the run (with a nearly 2.8-fold increase), and then declined on the following day, returning to baseline after 1 week. The value of high-density lipoprotein cholesterol (HDL-C) increased at the end of the run, peaked the day after and then slowly declined during the following days, to approximate the baseline concentration after 1 week. The values of total cholesterol and low-density lipoprotein cholesterol (LDL-C) declined after crossing the finishing line, reached the nadir 2 days after, but 1 week after the trial were still approximately 10% lower than the baseline concentration. These variations, firstly described in an elderly man running such a long distance, suggest that strenuous physical exercise generates considerable biochemical changes, triggering an acute prothrombotic state, which is then followed by a longer period of reduced cardiovascular risk.